2014
DOI: 10.4103/1305-7456.143630
|View full text |Cite
|
Sign up to set email alerts
|

An in-vitro evaluation of mechanical and esthetic properties of orthodontic sealants

Abstract: Objective:To evaluate mechanical and esthetic Properties of two commercially available orthodontic sealants: Opal®Seal (OS) and L.E.D. Pro Seal (PS).Materials and Methods:Discs of each sealant were prepared to test the following properties: Micro hardness, wear resistance and color stability. Samples were randomly selected after the wear test for SEM imaging to analyze surface morphology.Results:OS was significantly harder than PS (P < 0.001). PS was significantly more wear resistant than OS (P < 0.05). PS sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Application of surface sealant, unfilled low-viscosity resin, after polishing, may be an advanced method to ensure resin composite surfaces are smooth. [ 5 6 ] Recently, a liquid polishing system (BisCover LV, Bisco Inc., Schaumburg, IL, USA) has been introduced to reduce or eliminate the need for clinical polishing of restorations. BisCover LV is a light-curing resin used to seal restorations and is claimed to form a smooth polished surface without a sticky air-inhibited layer.…”
Section: Introductionmentioning
confidence: 99%
“…Application of surface sealant, unfilled low-viscosity resin, after polishing, may be an advanced method to ensure resin composite surfaces are smooth. [ 5 6 ] Recently, a liquid polishing system (BisCover LV, Bisco Inc., Schaumburg, IL, USA) has been introduced to reduce or eliminate the need for clinical polishing of restorations. BisCover LV is a light-curing resin used to seal restorations and is claimed to form a smooth polished surface without a sticky air-inhibited layer.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported the microhardness, resistance to wear and colour stability of these two sealants and they exhibited differences in wear abrasion resistance, hardness and discoloration . Our study demonstrated discoloration with food and drink was significantly higher with the PS, even though the efficacy of PS in reducing enamel demineralization was found to be 92% .…”
Section: Introductionmentioning
confidence: 52%
“…The sealants PS and OS have different amount of filler loading, OS with 38% and PS with 20%. The filler size was also different as observed under SEM in our previous study . Desired properties of orthodontic sealants include wear abrasion resistance, adequate hardness, colour stability, adequate F release, prevention of biofilm formation and resistance to acid penetration.…”
Section: Introductionmentioning
confidence: 69%
“…Considering such a value for a in vivo scenario, the results of ΔE1 obtained in this study can be considered within the limits of tolerance. Thus, the white-grey color of BNNTs seems to have no influence on the color of RBSs and the materials tested in this study had the ability to mask the white aspect of demineralized enamel 27 . As color remained similar to the sound enamel after sealing treatment, it is possible to use this material in aesthetic areas without compromising aesthetics.…”
Section: Discussionmentioning
confidence: 71%